Glue residue removing compound liquid and glue residue removing process

Through the synergistic role of the use of potassium hydroxide, tetrabinocyte ammonium hydroxide, dizenyl scholytic, dizomy, monocular ethyleine, and maltose, the existing existing existing gel residue composite solution has not strong cleaning ability The problem realizes more efficient photocolic glue removal and lower substrate corrosiveness.

CN119376199AActive Publication Date: 2025-01-28HUIZHOU JINSHENG NEW ELECTRONIC TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411647427.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-28
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The existing glue removal composite liquid has poor cleaning ability and has a long cleaning time.

Method used

Provides a dehuminar dehumination liquid, containing potassium hydroxide, cyt -b -basin ammonium oxide, dizenyl schochrome, ductinyle, single ethanol, and maltose. Through the synergies of these ingredients, the peeling efficiency of the dehumination complex solution is improved.

Benefits of technology

A significant improvement of the peeling efficiency of the deodorization residue, shortening the cleaning time, and reducing the corrosiveness of the substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005140012270000081
    Figure BDA0005140012270000081
  • Figure BDA0005140012270000091
    Figure BDA0005140012270000091
Patent Text Reader

Abstract

The invention relates to the technical field of chemical etching, and particularly discloses a glue residue removing compound liquid and a glue residue removing process. The degumming compound liquid is prepared from the following raw materials in parts by weight: 5 to 10 parts of potassium hydroxide, 2 to 4 parts of tetrabutyl ammonium hydroxide, 30 to 40 parts of dimethyl sulfoxide, 15 to 25 parts of pentaerythritol, 12 to 18 parts of monoethanolamine and 8 to 12 parts of maltose. The glue residue removing composite liquid prepared by the invention has relatively good stripping efficiency, all components are matched with a relatively good stripping photoresist, the corrosion to a base material is small, and the glue residue removing composite liquid has relatively stable corrosion resistance and stripping capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of chemical etching, and more specifically, to a desmearing composite liquid and a desmearing process. Background Art

[0002] The semiconductor manufacturing process includes grinding, etching, polishing, photolithography, cleaning and other steps. In the photolithography process, a layer of photoresist needs to be coated on the substrate. After ultraviolet exposure, the chemical properties of the photoresist change, and the circuit pattern is transferred from the mask to the photoresist. After the etching process, the circuit pattern is transferred from the photoresist to the substrate. After the pattern transfer is completed, the photoresist and its residues on the substrate need to be cleaned in order to proceed to the next step.

[0003] In the prior art, the desmearing composite solution used for photoresist stripping uses tetramethylammonium hydroxide (TMAH), dimethyl sulfoxide (DMSO), ethylene glycol (EG) and water to form an alkaline cleaning agent for cleaning photoresist. The cleaning agent is basically non-corrosive to metals. However, the cleaning ability is not strong and the cleaning time is long. Summary of the invention

[0004] In order to improve the problem that the desmear composite liquid has a weak cleaning ability and a long cleaning time, the present application provides a desmear composite liquid and a desmear process.

[0005] In the first aspect, the present application provides a composite liquid for removing sludge, which adopts the following technical solution: A desmearing composite liquid comprises the following raw materials by weight: 5-10 parts of potassium hydroxide, 2-4 parts of tetrabutylammonium hydroxide, 30-40 parts of dimethyl sulfoxide, 15-25 parts of pentaerythritol, 12-18 parts of monoethanolamine and 8-12 parts of maltose.

[0006] By adopting the above technical solution, potassium hydroxide can chemically react with the photoresist, causing the photoresist to swell and decompose, thereby achieving the dissolution and removal of the photoresist; tetrabutylammonium hydroxide, as an organic alkaline component, chemically reacts with the polymer in the photoresist, causing the photoresist to swell and decompose, thereby achieving effective dissolution and removal of the photoresist.

[0007] Dimethyl sulfoxide can effectively penetrate and dissolve the photoresist, promoting its stripping from the surface of the substrate. Dimethyl sulfoxide has good thermal stability, which enables it to remain stable during the stripping process. It is also easy to clean and will not leave residues on the substrate.

[0008] Pentaerythritol has good solubility and chemical stability, and can dissolve the polymer components in the photoresist, thereby promoting the dissolution and stripping of the photoresist. It also has certain surface activity, which can reduce the surface tension of the desmear composite liquid, help the desmear composite liquid to better penetrate into the interface between the photoresist and the substrate, and improve the stripping efficiency.

[0009] Monoethanolamine, as a co-solvent, can increase the solubility of photoresist in the solvent system and improve the dissolution rate, thereby enhancing the efficiency of the desmear composite liquid; it can also adjust the alkaline environment of the desmear composite liquid so that the desmear composite liquid has a lower corrosion ability to the substrate, and can provide more stable corrosion resistance and stripping ability.

[0010] In the process of photoresist stripping, maltose acts as an auxiliary stripping agent to adjust the alkaline environment of the system, and synergizes with monoethanolamine in the desmear compound liquid to reduce the alkalinity of the desmear compound liquid, reduce the corrosion of the desmear compound liquid to the substrate, and enhance the dissolution ability of the photoresist, so that the desmear compound liquid can more effectively penetrate into the interface between the photoresist and the substrate, promote the stripping of the photoresist, and improve the stripping efficiency of the photoresist. The various components cooperate with each other to jointly improve the stripping efficiency of the desmear compound liquid, and have low corrosion to the substrate.

[0011] Optionally, the mass ratio of potassium hydroxide, dimethyl sulfoxide and pentaerythritol is 1:5-7:2-4.

[0012] By adopting the above technical scheme, the mass ratio of potassium hydroxide, dimethyl sulfoxide and pentaerythritol is further limited within a certain range, and the compound of potassium hydroxide, dimethyl sulfoxide and pentaerythritol has a synergistic effect, and the degumming efficiency of the degumming residue composite liquid is jointly improved; potassium hydroxide can react chemically with the photoresist to make the photoresist swell and decompose, dimethyl sulfoxide can effectively penetrate and dissolve the photoresist, so that potassium hydroxide is fully in contact with the photoresist, the contact area between potassium hydroxide and the photoresist is increased, and the photoresist is effectively dissolved and removed; pentaerythritol reduces the surface tension of the degumming residue composite liquid, helps potassium hydroxide and dimethyl sulfoxide to better penetrate into the interface between the photoresist and the substrate, and improves the stripping efficiency.

[0013] Optionally, the mass ratio of tetrabutylammonium hydroxide, monoethanolamine and maltose is 1:6-8:2.5-3.5.

[0014] By adopting the above technical scheme, the mass ratio of tetrabutylammonium hydroxide, maltose and monoethanolamine is further limited within a certain range, and the combination of tetrabutylammonium hydroxide, maltose and monoethanolamine has a synergistic effect, and the degumming efficiency of the degumming slag composite liquid is jointly improved; tetrabutylammonium hydroxide reacts chemically with the polymer in the photoresist to cause the photoresist to swell and decompose, and the monoethanolamine adjusts the alkaline environment of the degumming slag composite liquid to reduce the corrosiveness of the degumming slag composite liquid to the substrate, and synergizes with the monoethanolamine to reduce the corrosion of the degumming slag composite liquid to the substrate, so that the tetrabutylammonium hydroxide effectively dissolves and removes the photoresist, and the combination of tetrabutylammonium hydroxide, maltose and monoethanolamine improves the removal efficiency of the photoresist and reduces the corrosion of the alkali solution to the substrate.

[0015] Optionally, the method for preparing maltose comprises the following steps: dispersing maltose in deionized water, stirring at a temperature of 80-85° C. for 20-30 min, adding sodium dodecylbenzene sulfonate, continuing stirring, and drying to obtain a mixture; The mixture is dispersed in deionized water, stirred at 25-30° C. for 1-2 hours, ethylenediaminetetraacetic acid and xylitol are added, stirred evenly, kept warm at 65-70° C. for 2-3 hours, dried, washed, and ground to obtain maltose.

[0016] By adopting the above technical solution, sodium dodecylbenzene sulfonate is a commonly used anionic surfactant with good detergency, wetting and dispersing properties. When sodium dodecylbenzene sulfonate is mixed with maltose, the surface activity of maltose and the surface activity of sodium dodecylbenzene sulfonate work synergistically to further reduce surface tension, enhance the wetting and penetration ability of the mixture, and help to subsequently cooperate with other components to reduce the stripping force between the photoresist and the substrate. Moreover, maltose and sodium dodecylbenzene sulfonate show a synergistic cleaning effect, improve the ability to remove stains, and help remove organic stains in the photoresist.

[0017] EDTA can combine with metal ions to form stable chelates, thereby preventing metal ions from interfering with the stripping process. At the same time, the chelating effect of EDTA can protect sodium dodecylbenzene sulfonate from the inhibition of metal ions, ensuring the cleaning performance of sodium dodecylbenzene sulfonate. Xylitol has swelling and dissolving effects. In the subsequent photoresist processing process, it helps the photoresist to swell and make its structure loose, making it easier to be dissolved and removed by other components in the desmearing composite solution.

[0018] Optionally, the mass ratio of maltose, sodium dodecylbenzenesulfonate, ethylenediaminetetraacetic acid and xylitol is 1:2-4:5-8:1.5-3.5.

[0019] By adopting the above technical scheme, the mass ratio of maltose, sodium dodecylbenzene sulfonate, ethylenediaminetetraacetic acid and xylitol is further limited within a certain range, the physical properties of maltose are improved, and maltose is combined with other components in the desmearing composite liquid to more effectively dissolve and strip the photoresist. The combination of maltose and sodium dodecylbenzene sulfonate enhances the wetting and penetration ability of the mixture, the chelating effect of ethylenediaminetetraacetic acid can protect sodium dodecylbenzene sulfonate from the inhibition of metal ions, and xylitol has swelling and dissolving effects. The combination of each component has a good effect of dissolving and removing the photoresist.

[0020] In a second aspect, the present application provides a preparation process of a desmearing composite liquid, comprising the following steps: mixing potassium hydroxide, tetrabutylammonium hydroxide, dimethyl sulfoxide, pentaerythritol, monoethanolamine and maltose, and then dispersing them in deionized water to obtain a desmearing composite liquid.

[0021] By adopting the above technical scheme, the preparation method of the desmear composite liquid is simple to operate and convenient to use, so that each component is mixed evenly, which is helpful to subsequently improve the efficiency of removing photoresist by the desmear composite liquid.

[0022] In a third aspect, the present application provides a desmearing process, comprising the following steps: (1) placing one side of the substrate containing the photoresist under ultraviolet light to obtain a treated substrate; (2) The aged substrate obtained in step (1) is placed in the above-mentioned desmear composite liquid for ultrasonic cleaning, then washed with deionized water, and dried with high-purity nitrogen.

[0023] By adopting the above technical scheme, the photoresist is first treated, and ultraviolet light can induce the breaking of chemical bonds in the photoresist molecules, promote the decomposition of the photoresist, and make it easier to remove. Then it is placed in a desmearing residue composite liquid and ultrasonically cleaned to remove the photoresist on the substrate, ensuring that the photoresist is completely removed and improving the photoresist stripping efficiency.

[0024] Optionally, in step (2), the ultraviolet light is provided by an ultraviolet lamp, the power of the ultraviolet lamp is 200-300 mW, and the treatment time is 50-60 s.

[0025] By adopting the above technical solution, using a UV lamp with a power of 200-300mW to remove photoresist is a specific photoresist removal technology, called photoresist stripping, which uses the energy of ultraviolet light to decompose or change the chemical structure of the photoresist, making it easier to remove the photoresist. When the power of the UV lamp is 200-300mW, it can provide sufficient energy density to accelerate the decomposition process of the photoresist, thereby promoting its removal.

[0026] Optionally, in step (2), the cleaning temperature is 70-75°C and the cleaning time is 1-3h.

[0027] By adopting the above technical scheme, the temperature and cleaning time of ultrasonic cleaning are controlled, so that the photoresist can be better removed. During the photoresist removal process, ultrasonic cleaning can effectively destroy the adhesion between the photoresist and the substrate by utilizing the mechanical effect and cavitation effect of ultrasound, thereby improving the photoresist removal efficiency. Ultrasonic cleaning can not only improve the photoresist removal efficiency, but also reduce the damage to the substrate material during the cleaning process, thereby ensuring high-quality production of devices.

[0028] Optionally, in step (2), the temperature of the deionized water washing is 30-35° C., and the washing time is 15-20 min.

[0029] By adopting the above technical solution, the appropriate deionized water washing temperature and time are defined, so that the photoresist residue can be better removed and the quality of the substrate is guaranteed.

[0030] In summary, this application has the following beneficial effects: 1. The various components in the present application cooperate with each other to jointly improve the stripping efficiency of the desmearing composite liquid, and have low corrosiveness to the substrate. Tetrabutylammonium hydroxide, as an organic alkaline component, chemically reacts with the polymer in the photoresist to cause the photoresist to swell and decompose, thereby achieving effective dissolution and removal of the photoresist. Dimethyl sulfoxide can effectively penetrate and dissolve the photoresist, promoting its stripping from the surface of the substrate. Dimethyl sulfoxide has good thermal stability, so that it can remain stable during the stripping process. At the same time, it is easy to clean and will not leave residues on the substrate.

[0031] 2. In the present application, potassium hydroxide can react chemically with the photoresist to swell and decompose the photoresist, thereby achieving the dissolution and removal of the photoresist; maltose is used as an auxiliary stripping agent to adjust the alkaline environment of the system, and synergizes with the monoethanolamine in the desmear composite liquid to reduce the alkalinity of the desmear composite liquid, reduce the corrosion of the desmear composite liquid to the substrate, and enhance the solubility of the photoresist, so that the desmear composite liquid can more effectively penetrate into the interface between the photoresist and the substrate, promote the stripping of the photoresist, and improve the stripping efficiency of the photoresist.

[0032] 3. In the present application, pentaerythritol has good solubility and chemical stability, can dissolve the polymer components in the photoresist, thereby promoting the dissolution and stripping of the photoresist, and also has a certain surface activity, which reduces the surface tension of the desmear composite liquid, helps the desmear composite liquid to better penetrate into the interface between the photoresist and the substrate, and improves the stripping efficiency. DETAILED DESCRIPTION

[0033] Preparation example of maltose Preparation Example 1-1 The preparation method of maltose comprises the following steps: dispersing 30 g of maltose in 50 mL of deionized water, stirring at a temperature of 85° C. for 25 min, adding sodium dodecylbenzene sulfonate, continuing stirring for 1 h, and drying to obtain a mixture; The mixture was dispersed in 100 mL of deionized water, stirred at 30° C. for 2 h, ethylenediaminetetraacetic acid and xylitol were added, stirred evenly, kept warm at 70° C. for 3 h, dried, washed, and ground to obtain maltose.

[0034] The mass ratio of maltose, sodium dodecylbenzenesulfonate, ethylenediaminetetraacetic acid and xylitol is 1:2:5:3.5.

[0035] Preparation Example 1-2 The difference from Preparation Example 1-1 is that sodium dodecylbenzenesulfonate is not added.

[0036] Preparation Example 1-3 The difference from Preparation Example 1-1 is that ethylenediaminetetraacetic acid is not added.

[0037] Preparation Example 1-4 The difference from Preparation Example 1-1 is that no xylitol is added.

[0038] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of maltose, sodium dodecylbenzenesulfonate, ethylenediaminetetraacetic acid and xylitol is 1:4:8:1.5.

[0039] Preparation Example 1-6 The difference from Preparation Example 1-1 is that the mass ratio of maltose, sodium dodecylbenzenesulfonate, ethylenediaminetetraacetic acid and xylitol is 1:8:2:4. Example

[0040] Example 1 A composite liquid for removing slag includes the following raw materials by weight: 5g potassium hydroxide, 4g tetrabutylammonium hydroxide, 40g dimethyl sulfoxide, 15g pentaerythritol, 12g monoethanolamine and 8g maltose.

[0041] Maltose was purchased from Wuhan Jinyixiang Fine Chemical Co., Ltd.

[0042] A method for preparing a desmearing composite liquid comprises the following steps: mixing potassium hydroxide, tetrabutylammonium hydroxide, dimethyl sulfoxide, pentaerythritol, monoethanolamine and maltose, and then dispersing them in 180g of deionized water to obtain the desmearing composite liquid.

[0043] Example 2 A desmearing composite liquid, which differs from Example 1 in that it comprises the following raw materials by weight: 10 g potassium hydroxide, 2 g tetrabutylammonium hydroxide, 30 g dimethyl sulfoxide, 25 g pentaerythritol, 18 g monoethanolamine and 12 g maltose.

[0044] Example 3 A composite liquid for removing slag, which is different from Example 1 in that maltose is prepared by Preparation Example 1-1.

[0045] Example 4 A composite liquid for removing slag, which is different from Example 3 in that maltose is prepared by Preparation Example 1-2.

[0046] Example 5 A desmearing composite liquid, which is different from Example 3 in that the maltose is prepared by Preparation Examples 1-3.

[0047] Example 6 A composite liquid for removing slag, which is different from Example 3 in that maltose is prepared by Preparation Examples 1-4.

[0048] Example 7 A composite liquid for removing slag, which is different from Example 3 in that maltose is prepared by Preparation Examples 1-5.

[0049] Example 8 A composite liquid for removing slag, which is different from Example 3 in that maltose is prepared by Preparation Examples 1-6.

[0050] Example 9 A composite liquid for removing slag, which is different from Example 3 in that the mass ratio of potassium hydroxide, dimethyl sulfoxide and pentaerythritol is 1:5:2.

[0051] Example 10 A composite liquid for removing slag, which is different from Example 3 in that the mass ratio of potassium hydroxide, dimethyl sulfoxide and pentaerythritol is 1:7:4.

[0052] Embodiment 11 A desmearing composite liquid, which is different from Example 3 in that the mass ratio of tetrabutylammonium hydroxide, monoethanolamine and maltose is 1:8:2.5.

[0053] Example 12 A desmearing composite liquid, which is different from Example 3 in that the mass ratio of tetrabutylammonium hydroxide, monoethanolamine and maltose is 1:6:3.5.

[0054] Comparative Example Comparative Example 1 A desmearing composite liquid, which is different from Example 3 in that potassium hydroxide is not added.

[0055] Comparative Example 2 A composite liquid for removing slag, which differs from Example 3 in that dimethyl sulfoxide is not added.

[0056] Comparative Example 3 A desmear composite liquid, which is different from Example 3 in that pentaerythritol is not added.

[0057] Comparative Example 4 A desmearing composite liquid, which differs from Example 3 in that tetrabutylammonium hydroxide is not added.

[0058] Comparative Example 5 A desmear composite liquid, which is different from Example 3 in that monoethanolamine is not added.

[0059] Comparative Example 6 A desmearing composite liquid, which differs from Example 3 in that maltose is not added.

[0060] Application Examples Application Example 1 A desmearing process comprises the following steps: (1) placing one side of the substrate containing the photoresist under ultraviolet light to obtain a treated substrate; (2) The aged substrate obtained in step (1) is placed in 100 g of a desmearing composite solution for ultrasonic cleaning, then washed with deionized water, and dried with high-purity nitrogen.

[0061] The substrate is a copper substrate with a size of 60*80 mm. The ultraviolet light is provided by an ultraviolet lamp with a power of 200 mW and a processing time of 60 s.

[0062] The cleaning temperature was 70°C and the cleaning time was 1 h.

[0063] The temperature of deionized water washing is 30°C and the washing time is 15 min.

[0064] The desmear composite liquid adopts the components of Example 1.

[0065] Application Example 2 A desmearing process, which is different from Application Example 1 in that the power of the ultraviolet lamp is 300 mW and the processing time is 50 s.

[0066] The cleaning temperature is 75°C and the cleaning time is 3h.

[0067] The temperature of deionized water washing is 35°C and the washing time is 20 min.

[0068] The desmear composite liquid adopts the components of Example 2.

[0069] Application Example 3 A desmearing process, which is different from Application Example 1 in that the desmearing composite liquid adopts the components of Example 3.

[0070] Application Example 4 A desmearing process, which is different from Application Example 1 in that the desmearing composite liquid adopts the components of Example 4.

[0071] Application Example 5 A desmearing process, which is different from Application Example 1 in that the desmearing composite liquid adopts the components of Example 5.

[0072] Application Example 6 A desmearing process, which is different from Application Example 1 in that the desmearing composite liquid adopts the components of Example 6.

[0073] Application Example 7 A desmearing process, which is different from Application Example 1 in that the desmearing composite liquid adopts the components of Example 7.

[0074] Application Example 8 A desmearing process, which is different from Application Example 1 in that the desmearing composite liquid adopts the components of Example 8.

[0075] Application Example 9 A desmearing process, which is different from Application Example 1 in that the desmearing composite liquid adopts the components of Example 9.

[0076] Application Example 10 A desmearing process, which is different from Application Example 1 in that the desmearing composite liquid adopts the components of Example 10.

[0077] Application Example 11 A desmearing process, which differs from Application Example 1 in that the desmearing composite liquid adopts the components of Example 11.

[0078] Application Example 12 A desmearing process, which is different from Application Example 1 in that the desmearing composite liquid adopts the components of Example 12.

[0079] Application Comparative Example 1 A desmearing process, which is different from Application Example 1 in that the desmearing composite liquid adopts the components of Comparative Example 1.

[0080] Application Comparative Example 2 A desmearing process, which is different from Application Example 1 in that the desmearing composite liquid adopts the components of Comparative Example 2.

[0081] Application Comparative Example 3 A desmearing process, which is different from Application Example 1 in that the desmearing composite liquid adopts the components of Comparative Example 3.

[0082] Application Comparative Example 4 A desmearing process, which is different from Application Example 1 in that the desmearing composite liquid adopts the components of Comparative Example 4.

[0083] Application Comparative Example 5 A desmearing process, which is different from Application Example 1 in that the desmearing composite liquid adopts the components of Comparative Example 5.

[0084] Application Comparative Example 6 A desmearing process, which is different from Application Example 1 in that the desmearing composite liquid adopts the components of Comparative Example 6.

[0085] Performance testing The performance of the substrates treated with the desmear process of Application Examples 1-12 and Comparative Examples 1-6 was tested. The corrosion of the lower wiring and the degree of stripping cleanliness of the prepared samples were observed under a SEM microscope. The test results are shown in Table 1.

[0086] Table 1 Test data of application examples and comparative examples Table 2 Test indicators Corrosion conditions: ○No corrosion Cleaning conditions: ○ Completely removed □ Slightly corroded □ Slightly residual ☆Minor corrosion ☆A small amount of residue △ Moderate corrosion More residue Combining the examples and the data in Table 1, it can be seen that the maltose used in Application Examples 1-2 is commercially available, and the prepared desmear composite liquid has a small amount of corrosion to the substrate in the desmear process. In the test results of Application Examples 1-2, there is a small amount of corrosion to the substrate, and the substrate cleaning results have a small amount of residue. Compared with Application Example 1, Application Examples 3 and Application Examples 7 replace maltose with maltose prepared by this application. In the test results, there is no corrosion to the substrate, and the substrate cleaning results completely remove the residue. It can be seen that the maltose prepared in this application has better comprehensive performance, can cooperate with monoethanolamine to reduce the alkalinity of the desmear composite liquid, reduce the corrosion of the desmear composite liquid to the substrate, and enhance the solubility of the photoresist, so that the desmear composite liquid can more effectively penetrate into the interface between the photoresist and the substrate, promote the stripping of the photoresist, and improve the stripping efficiency of the photoresist.

[0087] In the preparation process of maltose in Application Example 4, sodium dodecylbenzene sulfonate is not added. As can be seen from Table 1, compared with Application Example 3, in the test results, there is a small amount of corrosion to the substrate, and a small amount of residue is found in the substrate cleaning result, indicating that sodium dodecylbenzene sulfonate is mixed with maltose, and the surface activity of maltose and the surface activity of sodium dodecylbenzene sulfonate work synergistically to further reduce the surface tension and enhance the wetting and penetration ability of the mixture, which is helpful for the subsequent coordination with other components and reduces the stripping force between the photoresist and the substrate. Moreover, the combination of the two shows a synergistic cleaning effect, improves the ability to remove stains, and helps to remove organic stains in the photoresist.

[0088] In the preparation process of maltose in Application Example 5, ethylenediaminetetraacetic acid is not added. As can be seen from Table 1, compared with Application Example 3, in the test results, there is a small amount of corrosion to the substrate, and there is a small amount of residue in the substrate cleaning result, indicating that the chelating effect of ethylenediaminetetraacetic acid can protect sodium dodecylbenzene sulfonate from the inhibition of metal ions, ensuring the cleaning performance of sodium dodecylbenzene sulfonate, and can also combine with metal ions to form a stable chelate, thereby preventing metal ions from interfering with the stripping process.

[0089] In the preparation process of maltose in Application Example 6, xylitol was not added. As can be seen from Table 1, compared with Application Example 3, the test results showed a small amount of corrosion to the substrate, and a small amount of residue was found in the substrate cleaning results, indicating that xylitol has swelling and dissolving effects. In the subsequent photoresist processing process, it helps the swelling of the photoresist, making its structure loose, thereby making it easier to be dissolved and removed by other components in the desmear composite solution.

[0090] Application Example 8 changes the mass ratio of maltose, sodium dodecylbenzene sulfonate, ethylenediaminetetraacetic acid and xylitol. As can be seen from Table 1, compared with Application Examples 3 and 7, in the test results, there is a slight corrosion to the substrate, and the substrate cleaning result has a slight residue, indicating that the combination of maltose and sodium dodecylbenzene sulfonate enhances the wetting and penetration ability of the mixture, the chelating effect of ethylenediaminetetraacetic acid can protect sodium dodecylbenzene sulfonate from the inhibition of metal ions, and xylitol has swelling and dissolving effects. The combination of maltose, sodium dodecylbenzene sulfonate, ethylenediaminetetraacetic acid and xylitol has a good effect of dissolving and removing photoresist.

[0091] Application Examples 9-10 further limit the mass ratio of potassium hydroxide, dimethyl sulfoxide and pentaerythritol. Compared with Application Examples 3 and 7, the test results show that there is no corrosion to the substrate, and the substrate cleaning results completely remove the residue. Although the test results are the same, under SEM observation, Application Examples 9-10 treat the substrate more cleanly and without corrosion, and the substrate is brighter, indicating that the combination of potassium hydroxide, dimethyl sulfoxide and pentaerythritol has a synergistic effect. Potassium hydroxide can react chemically with the photoresist to swell and decompose the photoresist. Dimethyl sulfoxide can effectively penetrate and dissolve the photoresist, so that potassium hydroxide is fully in contact with the photoresist, increasing the contact area between potassium hydroxide and the photoresist, effectively dissolving and removing the photoresist, and pentaerythritol reduces the surface tension of the desmear composite liquid, helping potassium hydroxide and dimethyl sulfoxide to better penetrate into the interface between the photoresist and the substrate, thereby improving the stripping efficiency.

[0092] Application Examples 11-12 further define the mass ratio of tetrabutylammonium hydroxide, monoethanolamine and maltose. Compared with Application Examples 3 and 7, in the test results, there is no corrosion to the substrate, and the substrate cleaning results completely remove the residue. Although the test results are the same, under SEM observation, Application Examples 11-12 treat the substrate more cleanly and without corrosion, and the substrate is brighter, indicating that the combination of tetrabutylammonium hydroxide, maltose and monoethanolamine has a synergistic effect. Tetrabutylammonium hydroxide reacts chemically with the polymer in the photoresist to cause the photoresist to swell and decompose. Monoethanolamine adjusts the alkaline environment of the degumming composite liquid to reduce the corrosiveness of the degumming composite liquid to the substrate, and synergizes with monoethanolamine to reduce the corrosion of the degumming composite liquid to the substrate, so that tetrabutylammonium hydroxide can effectively dissolve and remove the photoresist. The combination of tetrabutylammonium hydroxide, maltose and monoethanolamine improves the removal efficiency of the photoresist and reduces the corrosion of the substrate by the alkaline solution.

[0093] No potassium hydroxide is added to the degumming slag composite liquid of Application Example 1. Compared with Application Example 3, the test results show that the substrate is slightly corroded and there are more residues in the substrate cleaning results, indicating that without adding potassium hydroxide, the corrosion of the substrate is significantly reduced, but the corresponding treatment results of the substrate are also worse, because potassium hydroxide can chemically react with the photoresist, causing the photoresist to swell and decompose, thereby achieving the dissolution and removal of the photoresist.

[0094] No dimethyl sulfoxide is added to the desmear composite liquid of Application Example 2. Compared with Application Example 3, in the test results, for moderate corrosion of the substrate, the substrate cleaning result has a small amount of residue, indicating that potassium hydroxide is more corrosive to the substrate, while dimethyl sulfoxide can effectively penetrate and dissolve the photoresist, promoting its stripping from the surface of the substrate. Dimethyl sulfoxide has good thermal stability, so that it can remain stable during the stripping process. At the same time, it is easy to clean and will not leave residue on the substrate.

[0095] No pentaerythritol is added to the desmear composite liquid of application example 3. Compared with application example 3, in the test results, for moderate corrosion of the substrate, there is a small amount of residue in the substrate cleaning result, indicating that potassium hydroxide is more corrosive to the substrate. Pentaerythritol has good solubility and chemical stability, can dissolve the polymer components in the photoresist, thereby promoting the dissolution and stripping of the photoresist, and also has certain surface activity, which reduces the surface tension of the desmear composite liquid, helps the desmear composite liquid to better penetrate into the interface between the photoresist and the substrate, and improves the stripping efficiency.

[0096] Tetrabutylammonium hydroxide is not added to the degumming slag composite liquid of Application Example 4. Compared with Application Example 3, in the test results, there is a small amount of corrosion to the substrate, and a small amount of residue is left after the substrate cleaning, indicating that tetrabutylammonium hydroxide, as an organic alkaline component, chemically reacts with the polymer in the photoresist, causing the photoresist to swell and decompose, thereby achieving effective dissolution and removal of the photoresist.

[0097] No monoethanolamine is added to the desmear composite liquid of Application Example 5. Compared with Application Example 3, the test results show that there is moderate corrosion to the substrate and there is more residue in the substrate cleaning result, indicating that monoethanolamine, as a co-solvent, can increase the solubility of the photoresist in the solvent system and increase the dissolution rate, thereby enhancing the efficiency of the desmear composite liquid; it can also adjust the alkaline environment of the desmear composite liquid, so that the desmear composite liquid has lower corrosion ability to the substrate, and can provide more stable corrosion resistance and stripping ability of the resist.

[0098] No maltose is added to the desmear composite liquid of Application Example 6. Compared with Application Example 3, the test results show that there is moderate corrosion to the substrate and there is more residue in the substrate cleaning result, indicating that maltose, as an auxiliary stripping agent, adjusts the alkaline environment of the system and synergizes with the monoethanolamine in the desmear composite liquid to reduce the alkalinity of the desmear composite liquid, reduce the corrosion of the desmear composite liquid to the substrate, and enhance the solubility of the photoresist, so that the desmear composite liquid can more effectively penetrate into the interface between the photoresist and the substrate, promote the stripping of the photoresist, and improve the stripping efficiency of the photoresist.

[0099] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. A composite liquid for removing slag, characterized in that: The raw materials are as follows, calculated by weight: 5-10 parts of potassium hydroxide, 2-4 parts of tetrabutylammonium hydroxide, 30-40 parts of dimethyl sulfoxide, 15-25 parts of pentaerythritol, 12-18 parts of monoethanolamine and 8-12 parts of maltose.

2. A desmearing composite liquid according to claim 1, characterized in that: The mass ratio of potassium hydroxide, dimethyl sulfoxide and pentaerythritol is 1:5-7:2-4.

3. A desmearing composite liquid according to claim 1, characterized in that: The mass ratio of the tetrabutylammonium hydroxide, monoethanolamine and maltose is 1:6-8:2.5-3.

5.

4. A desmearing composite liquid according to claim 1, characterized in that: The preparation method of maltose comprises the following steps: dispersing maltose in deionized water, stirring at a temperature of 80-85° C. for 20-30 minutes, adding sodium dodecylbenzene sulfonate, continuing stirring, and drying to obtain a mixture; The mixture is dispersed in deionized water, stirred at 25-30° C. for 1-2 hours, ethylenediaminetetraacetic acid and xylitol are added, stirred evenly, kept warm at 65-70° C. for 2-3 hours, dried, washed, and ground to obtain maltose.

5. A desmearing composite liquid according to claim 4, characterized in that: The mass ratio of maltose, sodium dodecylbenzene sulfonate, ethylenediaminetetraacetic acid and xylitol is 1:2-4:5-8:1.5-3.

5.

6. The method for preparing a desmear composite liquid according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: mixing potassium hydroxide, tetrabutylammonium hydroxide, dimethyl sulfoxide, pentaerythritol, monoethanolamine and maltose, and then dispersing them in deionized water to obtain a desmearing composite liquid.

7. A desmearing process comprising the following steps: (1) treating one side of a substrate containing a photoresist under ultraviolet light to obtain a treated substrate; (2) The aged substrate obtained in step (1) is placed in the desmear composite solution prepared in claim 6 for ultrasonic cleaning, then washed with deionized water and dried with high-purity nitrogen.

8. A desmearing process according to claim 7, characterized in that: In step (2), the ultraviolet light is provided by an ultraviolet lamp, the power of the ultraviolet lamp is 200-300 mW, and the treatment time is 50-60 s.

9. A desmearing process according to claim 7, characterized in that: In step (2), the cleaning temperature is 70-75°C and the cleaning time is 1-3h.

10. A desmearing process according to claim 7, characterized in that: In step (2), the temperature of the deionized water washing is 30-35°C, and the washing time is 15-20 minutes.

Citation Information

Patent Citations

  • Cleaning liquid for removing photoresist

    CN103869635A

  • Photoresist cleaning fluid

    CN105527802A

  • Photoresist cleaning agent and application

    CN115705001A

  • Stripping agent composition

    JP2004038073A

  • Photoresist Stripper

    US20190196337A1